Participation as pleasure: participatory culture of online audiences in reality television ‘Sing! China’ - Xie, Yuting; Yasin, Megat Al Imran; Shekh Alsagoff, Syed Agil; Ang, Lay Hoon (Redfame Publishing, 2025)
In the Information Era, audience participation has gradually become an important activity in the media field, including reality television. Under the present convergence of media and culture, it is also valuable to review the audiences themselves and their participation in regional contexts. This study adopts case study method using online observation of audiences in two Chinese social media platforms (Sina Weibo and Baidu Tieba), exploring the online audiences’ participation in ‘Sing! China’ and the participatory culture they formed during this process. Through this analysis, participation can be regarded as a sort of pleasure for online audiences, where the meanings of television programs can be creatively processed and utilized for daily entertainment or communication. To some extent, audiences’ interpretations of media texts are complicated, rather than being limited to mere acceptance or outright rejection as suggested by traditional models. Sometimes, audiences know the existence of authenticity issues in reality television (including performing authenticity of tutors) and some allow its coexistence within reality shows. In terms of authenticity issues on reality television, there are some audiences that create new cultural products based on their own watching experience and understanding that belongs to a part of popular culture, which is beyond the media content itself or may be different from what the media producers want to convey. Such audiences can also be viewed as media producers or free laborers of media not merely media consumers. All these individuals constitute a sort of participatory culture that circulates in society or exists in mass discourse. Through this study, the researcher attempts to provide a reference from the perspective of the audiences for the field of both academia and the media industry.